PERKEMBANGAN MATEMATIKA DALAM FILSAFAT DAN ALIRAN FORMALISME YANG TERKANDUNG DALAM FILSAFAT MATEMATIKA - Lily Parnabhakti; Marchamah Ulfa (Universitas Teknokrat Indonesia, 2020)
AbstractMathematics and philosophy have a pretty close relationship, compared to other sciences. The reason, philosophy is the base for learning science and mathematics is the mother of all sciences. There are also those who think that philosophy and mathematics are the mother of all existing sciences. In historical terms, the relationship between philosophy and mathematics experienced a very striking development. The question arises regarding